PENGANIAYAAN MAHASISWA BARU PADA KEGIATAN OSPEK KAMPUS DALAM TINJAUAN HAK ASASI MANUSIA DAN HUKUM PIDANA ISLAM - Syahputra, Yudha (Universitas Muhammadiyah Ponorogo, 2024)
Persecution of new students on campus is a problem that requires serious attention, especially from the perspective of Islamic Criminal Law and Human Rights. Bullying behaviour has a negative impact on individuals, involving physical, psychological, and social aspects that affect the academic development of new students. The research method used is empirical juridical research, otherwise known as field research, which aims to explore the applicable legal provisions and the reality that occurs in society by processing primary data in the field carried out after secondary data research. Theoretical foundations from experts and official guidelines such as laws and regulations constitute secondary data and prime data is obtained through field research with interviews. Persecution of new students on campus demands serious attention from the perspective of Islamic Criminal Law, human rights, and social justice. Prevention, such as prohibition of harmful orientation, close monitoring, sanctions, and character education, are important to create a safe campus environment. Implementation of character education and enforcement of penalties according to the classification of criminal offences are necessary. The need for serious and comprehensive efforts in handling and preventing violence in higher education is essential so that new students feel safe during their studies and the strengthening of campus policies and cross-sectoral cooperation to prevent the occurrence of maltreatment or other violence in Higher Education Institutions. The prevention of abuse is a moral responsibility in accordance with the principles of human values and the law in educational institutions. Measures such as the prohibition of harmful orientation, close monitoring, academic sanctions, and character education must be effectively implemented to create a safe and inclusive campus environment to ensure the basic rights of every individual.